Pancasila As Affirmations of Multicultural education In Indonesia - Hanpalam, Teodorikus; Leo Agung Sutimin; Triana Rejekiningsih (International Journal of Educational Research & Social Sciences, 2021)
The research is aimed at figuring Out The Values Of Pancasila And promoting The base of the multicultural education as well as the description of multicultural in Indonesia based on The Values Of The Pancasila. The research method used in this research is a method of qualitative research with a literate study research strategy. The sources and methods of data aggregation were collected from data in libraries, internet, scientific articles, books, journals and documents related to the themes of scientific research back up, published and published in scientific work. As a result of the study, the writings were used as a grade of bacaan and a recommendation for The development of multiculturaleducation in Indonesia. For the author of a general description of The Importance of Promoting multicultural education in Indonesia. Membership of the information is based on the description of multicultural education that is based on The Values Of Pancasila.